Analisis Profil Pemahaman Konsep dan Model Mental Siswa di SMA Kesatrian 2 Semarang pada Materi Interferensi dan Difraksi Cahaya (UPEJ Unnes Physics Education Journal, 2020)
This study aimed to determine the profile of students’ understanding of concepts and misconceptions and to identify the picture of students' mental models in explaining the phenomenon of light interference and diffraction. The type research is qualitative, and the research method used descriptive qualitative. Data collection techniques used observations and three tier multiple choices test and semi-structured interviews. The results showed that the conceptual understanding of students grade XI MIPA 2 at SMA Kesatrian 2 Semarang in the light interference and diffraction material was included in the conceptual understanding category of 30%, 48% misconception and 22% did not understand the concept. The profile of students' mental models based on Ifenthaler level category in explaining the material of light interference and diffraction included at the level of the surface. While the type of mental model is based on the type of Sendur is scientific mental model possessed by students only reached 2.38%. The remaining 97.62% classified as alternative mental models.